Proses Pembuatan Media Agar dari Bahan Alami untuk Bakteri dan Jamur - Siti Dwi Cahira; Ardi Mustakim (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
Agar is the main medium used in microbiology laboratories to grow bacteria and fungi because of its ability to form stable gels that are not easily degraded by microorganisms. However, the availability of expensive commercial agar and dependence on imports is a challenge for small-scale laboratories. This literature study aims to review the potential of natural materials such as local seaweed (Gracilaria sp.), banana peels, cassava starch, and coconut pulp as alternative media for microorganism growth. The results of the study indicate that Gracilaria has the ability to form gels similar to commercial agar, while banana peels and cassava starch are rich in nutrients but require the addition of thickeners. The main challenge lies in the sterilization process and media consistency. The use of these materials can be a cheap and sustainable solution in the development of microbiology media based on local resources.